2000
DOI: 10.1902/jop.2000.71.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Subantimicrobial Dose Doxycycline Improves the Efficacy of Scaling and Root Planing in Patients With Adult Periodontitis

Abstract: The adjunctive use of SDD with SRP is more effective than SRP alone and may represent a new approach in the long-term management of AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
228
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(258 citation statements)
references
References 31 publications
22
228
1
7
Order By: Relevance
“…In several studies, the inhibitor effects of doxycycline on matrix degrading MMP activities have been demonstrated (7,8). The results have indicated that this host-modulating antibiotic as an adjunct to SRP has also provided more successful clinical healing results than SRP alone (47,55). Recently, one of these studies has shown that improvements in PD and CAL were significantly greater with adjunctive SDD than with adjunctive placebo and it was concluded that the adjunctive use of doxycycline with SRP is more effective than SRP alone, which is in contrast to our findings (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, the inhibitor effects of doxycycline on matrix degrading MMP activities have been demonstrated (7,8). The results have indicated that this host-modulating antibiotic as an adjunct to SRP has also provided more successful clinical healing results than SRP alone (47,55). Recently, one of these studies has shown that improvements in PD and CAL were significantly greater with adjunctive SDD than with adjunctive placebo and it was concluded that the adjunctive use of doxycycline with SRP is more effective than SRP alone, which is in contrast to our findings (55).…”
Section: Discussionmentioning
confidence: 99%
“…The results have indicated that this host-modulating antibiotic as an adjunct to SRP has also provided more successful clinical healing results than SRP alone (47,55). Recently, one of these studies has shown that improvements in PD and CAL were significantly greater with adjunctive SDD than with adjunctive placebo and it was concluded that the adjunctive use of doxycycline with SRP is more effective than SRP alone, which is in contrast to our findings (55). However, in those studies, low-dose doxycycline treatments were used for much longer time periods (6-9 months).…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline was discovered in the early 1960's as a semisynthetic long-acting tetracycline derivative useful as a bacterial ribosome inhibitor in a wide variety of microbes. In subantimicrobial doses it is also an effective primary treatment for rosacea, sterile corneal ulceration, and effective adjunctive treatment for adult periodontitis (84)(85)(86) . Doxycycline has been shown to effectively inhibit MMP-9 in a wide variety of mouse and human cells including prostate epithelium, epidermal keratinocytes, and the aortic endothelium (87)(88)(89)(90) .…”
Section: Tetracyclines and Their Derivativesmentioning
confidence: 99%
“…[15][16][17] Therefore, the aim of this review was to compare the effects of adjunctive use of NSAIDs with nonsurgical periodontal treatment (NSPT) on periodontal disease based on the available literature. Following focused question was addressed: "In patients with periodontal disease, is there an additional benefit of the oral administration of NSAIDs adjunctive with NSPT compared to control in terms of the clinical attachment level (CAL), probing depth (PD), and adverse outcomes in randomized controlled trials?…”
Section: Introductionmentioning
confidence: 99%